"Cada uno a su ayllu": orden y sacrificio en Diamantes y pedernales - Galván- Díaz, F.J. (El Colegio de México, 2024)
In this article, I offer a new reading of José María Arguedas’ Diamantes y Pedernales based on Polysystem Theory. Applying this theory, I hope to establish the way in which the social groups represented in the novel coexist, to identify the mechanisms of the order they introduce, as well as to point to the tools they use to repair the attacks on the community’s system. This approach allows us to understand that, although the novel is said to revolve around white figures, the order in fact privileges the indigenous world.